The larger attachment glycoprotein of respiratory syncytial virus produced in primary human bronchial epithelial cultures reduces infectivity for cell lines. - Tiffany King; Asuncion Mejias; Octavio Ramilo; Mark E Peeples (PLoS Pathogens)
Respiratory syncytial virus (RSV) infects the upper and lower respiratory tracts and can cause lower respiratory tract infections in children and elders. RSV has traditionally been isolated, grown, studied and quantified in immortalized cell lines, most frequently HEp-2 cells. However, in vivo RSV infection is modeled more accurately in primary well differentiated human bronchial epithelial (HBE) cultures where RSV targets the ciliated cells and where the putative RSV receptor differs from the receptor on HEp-2 cells. The RSV attachment (G) glycoprotein in virions produced by HEp-2 cells is a highly glycosylated 95 kDa protein with a 32 kDa peptide core. However, virions produced in HBE cultures, RSV (HBE), contain an even larger, 170 kDa, G protein (LgG). Here we show that LgG is found in virions from both subgroups A and B lab-adapted and clinical isolates. Unexpectedly, RSV (HBE) virions were approximately 100-fold more infectious for HBE cultures than for HEp-2 cells. Surprisingly, the cause of this differential infectivity, was reduced infectivity of RSV (HBE) on HEp-2 cells rather than enhanced infectivity on HBE cultures. The lower infectivity of RSV(HBE) for HEp-2 cells is caused by the reduced ability of LgG to interact with heparan sulfate proteoglycans (HSPG), the RSV receptor on HEp-2 cells. The discovery of different infectivity corresponding with the larger form of the RSV attachment protein when produced by HBE cultures highlights the importance of studying a virus produced by its native host cell and the potential impact on quantifying virus infectivity on cell lines where the virus entry mechanisms differ from their natural target cell.